Detection of Coxiella burnetii (Gammaproteobacteria: Coxiellaceae) in ticks collected from infested dogs in Kerman, Southeast of Iran - Mohammad Khalili; Mahdieh Rezaei; Baharak Akhtardanesh; Zeinab Abiri; Shima Shahheidaripour (Persian Journal of Acarology)
Q fever, as one of the tick-borne zoonotic diseases, is caused by Coxiella burnetii. Ticks may play an important role in C. burnetii transmission to animals and humans. By using nested Trans-PCR, we investigated the presence of C. burnetii in ticks collected from dogs in Kerman, southeast of Iran. A total of 375 ticks were randomly collected from 100 dogs. Eight pools were finally formed. The pools of tick samples were assessed for the presence of C. burnetii. Genomic DNA extraction was done and samples were evaluated by nested Trans-PCR. All tick specimens were identified as Rhipicephalus sanguineus regarding the taxonomical characteristics. Coxiella burnetii was detected in 1 out of 8 (12.5%) pool samples. One positive sample was subjected to sequence analysis, which successfully confirmed the accuracy of the PCR assay. Our data show that ticks infesting dogs can be infected by C. burnetii, providing zoonotic importance of these populations. Efforts should be focused on understanding the role and epidemiologic importance of dogs and their ticks, especially for human Q fever, which can be a life-threatening disease.